2022
DOI: 10.4196/kjpp.2022.26.6.541
|View full text |Cite
|
Sign up to set email alerts
|

Gaseous signal molecule SO2 regulates autophagy through PI3K/AKT pathway inhibits cardiomyocyte apoptosis and improves myocardial fibrosis in rats with type II diabetes

Abstract: Myocardial fibrosis is a key link in the occurrence and development of diabetic cardiomyopathy. Its etiology is complex, and the effect of drugs is not good. Cardiomyocyte apoptosis is an important cause of myocardial fibrosis. The purpose of this study was to investigate the effect of gaseous signal molecule sulfur dioxide (SO 2 ) on diabetic myocardial fibrosis and its internal regulatory mechanism. Masson and TUNEL staining, Western-blot, transmission electron microscopy, RT-qPCR, imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Zhao et al . [ 60 ] also reported a decrease in endogenous SO 2 production in cardiomyocytes following high glucose stimulation. The results observed in this study suggested that administration of exogenous SO 2 donors significantly improved the myocardial fibrosis in hyperthyroid rats, restricted the ERS-activated, and inhibited apoptosis in cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al . [ 60 ] also reported a decrease in endogenous SO 2 production in cardiomyocytes following high glucose stimulation. The results observed in this study suggested that administration of exogenous SO 2 donors significantly improved the myocardial fibrosis in hyperthyroid rats, restricted the ERS-activated, and inhibited apoptosis in cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, miR-34a decreases lipid absorption, lipogenesis, and autophagy by activating the sirtuin 1 (SIRT1)-mediated sterol regulatory element-binding transcription factor 1c (SREBP1c) signaling pathway ( Fig. 2B ) [ 52 , 53 ].…”
Section: Inflammatory Signaling Pathways Under Liver Injurymentioning
confidence: 99%
“…Myocardial fibrosis is the primary pathological change in DCM [ 3 , 4 ]. The pathological features of myocardial fibrosis involve excess deposition of extracellular matrix (ECM) [ 5 ], resulting in the thickening and stiffness of the cardiac walls increased, leads to heart failure, cardiac dysfunction, arrhythmias, and heart attacks, and eventually cardiovascular death. [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%